Etnobotani Keanekaragaman Jenis Tumbuhan Obat Tradisional dari Hutan di Desa Pakuli Kecamatan Gumbasa Kabupaten Donggala, Sulawesi Tengah - Eny Yuniati; Muhammad Alwi (Biocelebes, 2010)
This research has aim to knows diversity and plant species of jungle as used to medical plants in Pakuli village. Method used this research is analisis vegetation and using of index culture significans culture (ICS) with to following Turner procedure (1988). From yield this research has a 70 species medical plants from 48 famili, and rhizomes species has a high score ICS as a 70. Key words: Diversity, medical plants, Pakuli village.